The Role of Subthreshold Micropulse Yellow Laser as an Alternative Option for the Treatment of Refractory Postoperative Cystoid Macular Edema - Verdina, Tommaso (J Clin Med, 2020)
Background: To evaluate the efficacy and the safety of subthreshold micropulse yellow laser (SMYL) in the treatment of chronic postoperative cystoid macular edema (PCME), which is refractory to standard therapies. Methods: A retrospective chart review of ten eyes of ten patients affected by refractory PCME who underwent SMYL was performed. Five PCME cases were subsequent to uncomplicated cataract surgery (CS), two cases to complicated CS (CCS) with posterior capsule rupture and three cases occurred after retinal detachment surgery (RD). All conditions were refractory to conventional treatments prior to SMYL interventions for at least 4 months, including nonsteroidal anti-inflammatory eyedrops, topical steroids, oral indomethacin, sub-Tenon’s triamcinolone injections and Dexamethasone intravitreal implants. All patients underwent one or more treatments with 577 nm SMYL photo-stimulation, with 7 × 7 grids with confluent spots and a 5% duty cycle covering the whole edematous retina, including the foveal center. Best corrected visual acuity (BCVA) and central macular thickness (CMT) were obtained using OCT, and evaluated before and after the treatment at 1, 2, 3 and 6-month follow-ups. Results: A complete subfoveal macular edema resolution was observed in all of the eyes, with statistically significant improvements in terms of BCVA and CMT in all of the follow-up timelines (at 6 months, p = 0.002 and p = 0.005, respectively). The mean number of laser treatments was 1.3. At the final follow-up, a complete subfoveal edema reabsorption was observed in all patients with visual acuity improvement. No complications were observed in any case. Conclusions: SMYL seems to be a safe and effective treatment for the long-term resolution of refractory PCME and may be a useful alternative to expensive and invasive therapeutic options.